Hobi-Like Pestivirus in Aborted Bovine Fetuses - Decaro, Nicola (American Society for Microbiology, 2012)
An outbreak of abortion affecting multiparous cows was associated with Hobi-like pestivirus infection. Viral RNA and antigens were detected in the tissues of two aborted fetuses. Molecular assays for other common abortogenic agents tested negative. At the genetic level, the Hobi-like pestivirus displayed the closest relatedness to Italian, Australian, and South American viruses, whereas it diverged from the prototype Thai isolate. These findings may have important implications for the pestivirus control/eradication programs in cattle herds.